Immunosuppressive factors from lymphoid cells of nonresponder mice primed with L-glutamic acid60-L-alanine30-L-tyrosine10. IV. Lack of strain restrictions among allogeneic, nonresponder donors and recipients (The Rockefeller University Press, 1978)
The synthetic terpolymer of L-glutamic acid60-L-alanine30-L-tyrosine10 (GAT) fails to stimulate development of GAT-specific antibody responses in nonresponder mice but stimulates development of GAT-specific suppressor T cells that inhibit the development of normal anti-GAT plaque-forming cell responses to GAT complexed to methylated bovine serum albumin (MBSA). Extracts from lymphoid cells of GAT-primed but not control, nonresponder (DBA/1) mice contain a T-cell factor (GAT- TsF) that also specifically suppresses responses to GAT-MBSA by normal syngeneic spleen cells. The experiments reported in this communication demonstrate that: (a) extracts from all GAT-primed nonresponder mice tested contain GAT-TsF; (b) non-H-2 genes do not restrict the production of GAT-TsF; (c) all nonresponder strains of mice regardless of their non-H-2 genes are suppressed by GAT-TsF from all other strains bearing the nonresponder H-2p,q,s haplotypes; (d) suppression of GAT- MBSA responses by both syngeneic and allogeneic nonresponder spleen cells is mediated by a molecule encoded by the H-2 gene complex; and (e) both syngeneic and allogeneic nonresponder mice are suppressed by purified GAT-TsF that lacks immunoreactive GAT.